Four times out of Europe: Serial invasions of the winter moth, Operophtera brumata , to North America - Jeremy C. Andersen; Nathan P. Havill; Adalgisa Caccone; Joseph S. Elkinton (Molecular Ecology, 2021)
Reconstructing the geographic origins of non‐native species is important for studying the factors that influence invasion success, however; these analyses can be constrained by the amount of diversity present in the native and invaded regions, and by changes in the genetic background of the invading population following bottlenecks and/or hybridization events. Here we explore the geographical origins of the invasive winter moth ( Operopthera brumata L.) that has caused widespread defoliation to forests, orchards, and crops in Nova Scotia, British Columbia, Oregon, and the northeastern United States. It is not known whether these represent independent introductions to North America, or a “stepping stone” spread among regions. Using a combination of Bayesian assignment and approximate Bayesian computation methods, we analysed a population genetic data set of 24 microsatellite loci. We estimate that winter moth was introduced to North America on at least four occasions, with the Nova Scotian and British Columbian populations probably being introduced from France and Sweden, respectively; the Oregonian population probably being introduced from either the British Isles or northern Fennoscandia; and the population in the northeastern United States probably being introduced from somewhere in Central Europe. We discuss the impact of genetic bottlenecks on analyses meant to determine region of origin.